Eco-Enzyme Innovation: Transforming Pineapple Waste into Sustainable Cleaning Liquids through Community Empowerment in Tangkit Baru Village - Surhaini, Surhaini; Lisani, Lisani; Emanauli, Emanauli; Fiardilla, Fauziah; Suseno, Rahayu; Rinaldi, Rinaldi (LPPM Universitas Jambi, 2025)
Tangkit Baru Village is a major pineapple production center in Jambi, yielding over 728,000 quintals annually. However, this massive production generates significant organic waste from local home industries, which remains largely unmanaged. This community service program aimed to address this environmental challenge by empowering the Women’s Farmers Group (locally known as Kelompok Wanita Tani or KWT) through eco-enzyme technology. The program was implemented in four stages: Survey, Socialization, Technical Training (using a 1:3:10 fermentation ratio), and a three-month Mentoring phase. The results demonstrated a significant impact, with participants' knowledge increasing by 41.1% (from 45.3% to 86.4%). Technical success was high, with 80% of participants successfully producing quality eco-enzymes (pH < 4.0). Furthermore, 90% of participants adopted the liquid for household cleaning, indicating a profound behavioral shift. This program proves that eco-enzyme technology is a feasible, low-cost solution for agro-industrial waste recovery while enhancing community resilience and sustainable waste management practices.